Electrochemical Properties and Analyses of CeCl3 in LiCl-KCl Eutectic Salt. Issue 10 (24th July 2015) - Yoon, D.; Phongikaroon, S.
Abstract : Thermodynamic and electrochemical properties of cerium in LiCl-KCl eutectic salt have been measured and studied at different concentrations (0.5 – 4 wt%) and temperatures (698 K – 798 K) via both cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) techniques as a part of developing a fundamental understanding and methodology in materials detection and accountability for pyroprocessing technology. CV experiments were performed to determine the diffusion coefficient and apparent standard potential of CeCl3 on the tungsten working electrode. The diffusion coefficient was calculated by using Delahay equation, and raging from 0.48 × 10 −5 to 1.01 × 10 −5 cm 2 s −1 . Results reveal that the calculated diffusion coefficient of CeCl3 in the salt follows the Arrhenius temperature relationship and it is weakly affected by the changes in concentration of CeCl3 . The apparent standard potentials were calculated from peak potentials showing linear relationship with temperature. Exchange current density values of Ce 3+ /Ce couple in the salt were obtained from EIS experiments, ranging from 0.0076 A cm −2 to 0.18 A cm −2 . The results indicate that these values follow Arrhenius temperature dependence and increase when CeCl3 concentration increases.